2019
DOI: 10.1590/1413-81232018241.35052016
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento sobre o diabetes e atitude para o autocuidado de idosos na atenção primária à saúde

Abstract: This study aimed to assess the knowledge about diabetes, the attitude for self-care and associated factors through a cross-sectional study, the baseline of a randomized clinical trial with elderly diabetic in primary health care in Recife, Northeastern Brazil. We used the Diabetes Knowledge Scale (DKN-A) and Diabetes Attitudes Questionnaire . Of the 202 elderly, 77.7% had insufficient knowledge of the disease, especially for ketonuria, food replacement and were unaware of the causes and care of hypoglycemia. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1
40

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 23 publications
1
33
1
40
Order By: Relevance
“…However, the SABE study found out that the higher the survival of the elderly, the higher the level of education (31) . Hence, we inferred that, since education is a determining and conditioning factor of health, low education can compromise the health self-care of the elderly (32) . Moreover, individuals with high education levels may have better access to advantages and health services that ensure their quality of life and good health status (33) .…”
Section: Resultsmentioning
confidence: 96%
“…However, the SABE study found out that the higher the survival of the elderly, the higher the level of education (31) . Hence, we inferred that, since education is a determining and conditioning factor of health, low education can compromise the health self-care of the elderly (32) . Moreover, individuals with high education levels may have better access to advantages and health services that ensure their quality of life and good health status (33) .…”
Section: Resultsmentioning
confidence: 96%
“…A maior parte da sua amostra, equivalente a 47,6% (n=50), possuía o ensino fundamental completo. Nesse aspecto, Borba et al (2019), ao avaliar o conhecimento sobre diabetes e atitude para o autocuidado de idosos na atenção primária em saúde no Nordeste do Brasil, atribuíram a baixa escolaridade como fator de risco para conhecimento insuficiente e atitude negativa quanto ao autocuidado.…”
Section: Resultsunclassified
“…According to the self-care model, it is possible to enhance the patient's ability to acquire greater independence and autonomy over their treatment, as well as a greater burden of responsibility, aiming at improving the understanding and acceptance of the necessary care for life maintenance and general well-being. 15 To be successful in implementing care practices, it is necessary to consider the personal and human characteristics of nurses, and the age range is one of them. In this study, unlike others, the age of these professionals was intermediate (42 ± 9 years old), while in other scientific evidence directed to PHC nurses, the age group identified was younger, i.e., 20 to 30 years old 16 and 26 to 30 years old.…”
Section: Discussionmentioning
confidence: 99%